Clay-shoveler's fracture: A snapshot. (July 2016) - Toman, E; Beaven, A; Harland, S; Porter, K
The clay-shoveler's fracture is a stable oblique fracture through the spinous process of a lower cervical vertebra, classically C6 or C7. Diagnosed on plain radiograph, computed tomography and occasionally magnetic resonance imaging, the injury is most commonly seen in road traffic collisions in the modern-day. A stable injury, the clay-shoveler's fracture is managed non-operatively and requires symptomatic treatment only. This short article examines the history surrounding the injury and provides a comprehensive overview of the clay-shoveler's fracture for the non-spinal surgeon.